Educação Ambiental na escola da comunidade Kaingang de Marrecas – Turvo/PR - Barreto, Helen Leandra (2017)
The present research had the purpose of analyzing the educational processes of Environmental Education in the context of the Indigenous School Education of the village of Marrecas in Turvo-PR, with theoretical foundation of Piaget in socioocentrada education and Freire in emancipatory and libertarian education, besides Veiga and Faustino who Provides the critical basis of Indigenous School Education, which has its own legislation that gives the community autonomy in the school space, and a flexible teaching to its specificities and peculiarities. The research is ethnographic based on participatory observations with interventions and interviews in the school space, which includes the participation of teachers, managers, pedagogical team and other professionals, indigenous and non-indigenous. The analysis was theoretically referenced to the constitutive principles of this educational dimension: cooperation and reciprocity, ethics and responsibility, emancipatory autonomy, environmental sustainability, transversality and interdisciplinarity. The results evidenced that the identity of Piaget's thinking about socio-entertained education that comes from the social perspective of the indigenous community that values collective, cooperation and reciprocity, as well as the thinking of Paulo Freire with a critical conception of Environmental Education, Conception of being human, while unfinished, relational and ethical, responsible and part of nature; This relationship of identity corroborates the vision of interdependence of the human being and the natural environment, of the social, economic and cultural factors for the construction of an ecological subject that manages to relate these elements in a critical way by the awareness. The research focuses on contextualizing the local environment for the construction of Critical Environmental Education, since dealing with environmental issues as experiences and local experiences of the subjects, reveals real alternatives for overcoming and preventing problems. Thus, the socio-pedagogical conception has as a methodological basis the dialogue between educators and learners, always problematized with the context, and thus, leading to environmental education in a new perspective, which transcends pragmatic content education but allows intellectual autonomy , Provokes the senses and the sharpness to understand the totality, in this way promotes an awareness because it places the subject within the environmental problematic, inserted in it, its role goes from supporting the protagonist in the transformation of the world, so that it is a more Fair, sustainable, supportive and self-conscious.